C78 PREVALENCE AND MECHANISMS OF SEVERE MITRAL AND TRICUSPID REGURGITATION IN A HEART FAILURE OUTPATIENTS POPULATION. (18th May 2022) - Pugno Vanoni, F; Biroli, M; Cannata, F; Pagliaro, B; Pellegrino, M; Villaschi, A; Gasparini, G; Ardino, L; Vrinceanu, E; Loiacono, F; Pini, D
Abstract: Introduction: Mitral regurgitation (MR) and tricuspid regurgitation (TR) are a known cause of morbidity and mortality in heart failure (HF) patients. Maximal up–titration of guideline–directed medical therapy (GDMT) for HF may not be enough to reduce the severity of the valve's incompetence and patients' symptoms. The development and successful results of transcatheter therapies for mitral/tricuspid disease have opened new therapeutic opportunities when surgery is not feasible. Accurate valve regurgitation's mechanisms evaluation is essential to choose the best treatment option. This study aims at evaluating the prevalence and underlying mechanisms of at least moderate–to–severe (≥3+/4+) MR and/or TR in a cohort of HF outpatients. Methods: We retrospectively analyzed the medical records of 1260 outpatients evaluated by our HF unit between January 2020 and June 2021. All patients with echocardiographic evidence of ≥ 3+/4+ MR and/or TR were included (treated ones were excluded), and a thorough echocardiographic images review was conducted. A full collection of patients' clinical, laboratory and therapy regimens details was performed as well. Results: Of the 1260 analyzed patients, 173 (13.7%) exhibited ≥3+/4+ MR and/or TR and were included in the registry. Table 1 shows the main clinical/echocardiographic characteristics. Mean age was 80±7 years, median ejection fraction was 45% (IQR=33–55). All patients were treated with maximal tolerated doses of GDMT and, if appropriate, with cardiac devices/myocardial revascularization. ≥3+/4+ MR and/or TR was observed in 92 (7.3%) and 117 (9.3%) patients, respectively. Patients with isolated significant MR were 56 (4.4%), with isolated significant TR were 81 (6.4%); the remaining 36 (2.8%) had both MR/TR. Among patients with significant MR, 50 (54%) had functional/secondary valvular defect (details in Figure 2 ): the majority (41, 82%) presented a ventricular etiology (asymmetric tethering in 18/41) while 9 (18%) an atrial one (atriogenic tethering in 3/9). Conclusion: Despite optimized GDMT, the prevalence of patients with hemodynamically significant valvular defects was considerably high in our HF population. This is the first registry to comprehensively detail atrioventricular valve regurgitations' mechanisms in a wide real–life cohort of HF outpatients. Further studies are needed to identify reasons for potential undertreatment and patients who would benefit the most from percutaneous correction of their valvular defects.